(untitled) (Jurnal Psikologi Udayana, 2025)
The phenomenon of alcohol consumption among male adolescents in RT X, Palembang, shows an increasing trend and is commonly carried out in groups. In general, adolescence is a developmental stage in which peer influence is particularly strong, leading adolescents to adjust their attitudes and behaviors to group norms in order to gain social acceptance. However, empirical observations among male adolescents in RT X, Palembang, reveal a high intensity of alcohol consumption driven by peer pressure and conformity, which contradicts expectations of healthy and adaptive adolescent development. This study aims to examine the relationship between the intensity of alcohol consumption and peer conformity among male adolescents. The proposed hypothesis is that there is a significant relationship between the intensity of alcohol consumption and peer conformity. This research employs a quantitative approach with a correlational design. The participants were male adolescents residing in RT X, Palembang, selected using a total sampling technique. Data were collected using an alcohol consumption intensity scale and a peer conformity scale. Data analysis was conducted using correlation techniques to determine the direction and strength of the relationship between variables. The results indicate a positive and significant relationship between the intensity of alcohol consumption and peer conformity, meaning that higher levels of peer conformity are associated with higher levels of alcohol consumption intensity. These findings suggest that social pressure and the need for peer acceptance play an important role in shaping risky behaviors among adolescents. The implications of this study highlight the importance of peer-based interventions, family involvement, and community prevention programs to reduce alcohol consumption behavior among adolescents.